2017
DOI: 10.1177/0141076817738502
|View full text |Cite
|
Sign up to set email alerts
|

Why doctors consider leaving UK medicine: qualitative analysis of comments from questionnaire surveys three years after graduation

Abstract: Objective: To report the reasons why doctors are considering leaving medicine or the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 9 publications
(14 reference statements)
0
58
0
1
Order By: Relevance
“…18,19 In the UK, the key outcomes associated with mental ill-health in doctors include presenteeism (doctors working despite being unwell), [20][21][22] absenteeism (doctors taking sickness leave frequently, which could result in gaps in the service) 23 and workforce retention issues (doctors leaving the NHS either temporarily or permanently). [24][25][26][27] There is growing interest among different organisations and journals in understanding and addressing the issue of mental ill-health in doctors. This spans from the British Medical Journal collection on doctors' well-being 28 to the Health Education England's NHS Staff and Learner's Mental Wellbeing Commission.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 In the UK, the key outcomes associated with mental ill-health in doctors include presenteeism (doctors working despite being unwell), [20][21][22] absenteeism (doctors taking sickness leave frequently, which could result in gaps in the service) 23 and workforce retention issues (doctors leaving the NHS either temporarily or permanently). [24][25][26][27] There is growing interest among different organisations and journals in understanding and addressing the issue of mental ill-health in doctors. This spans from the British Medical Journal collection on doctors' well-being 28 to the Health Education England's NHS Staff and Learner's Mental Wellbeing Commission.…”
Section: Discussionmentioning
confidence: 99%
“…Exemplar quotations are provided along with year the participant started their F3 and participant identifier. [1][2][3][4][5]…”
Section: Data Interpretationmentioning
confidence: 99%
“…There is limited qualitative research relating to reasons why UK junior doctors take time out of training. Lambert et al 4 conducted a cross-sectional questionnaire survey, aimed at establishing why doctors consider working abroad. The sampling frame was all UK doctors who graduated in 2008 and in 2012, with 5291 respondents.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of studies of motivations for early retirement suggested that high workload and burnout can lead to doctors' earlier retirement. 7 Given recent uncertainty around NHS contracts, 8,9 and the UK's impending exit from the EU, 10 it is timely to update knowledge in this area with regard to UK-trained doctors.…”
Section: Introductionmentioning
confidence: 99%